STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI LANGKAH PENANGGULANGAN BENCANA DI DESA PERESAK, LOMBOK TENGAH - Augustina, Rizaka; Istiana; Dwinanda, I.; Rosalia, N.A.; Asmayani, N. (Universitas Mataram, 2024)
The geographical location and conditions in Peresak Village are the main factors that cause potential natural disasters. If you look at the area where many rivers flow (river catchment areas) and there are highlands at a number of points, there are potential disasters such as floods and landslides that can occur at any time. Reflecting on the existing potential, knowledge regarding disaster risk mitigation or management is very necessary to be provided to the Peresak Village community so that they can fully understand the conditions of the area where they live and be able to take appropriate action in the context of disaster response. The method of implementing service is the observation and lecture method. This service is also guided by the PKM approach to Participatory Action Research (PAR). The service work program that has been carried out includes socializing disaster management, reforestation, cleaning, and making plans for evacuation routes, gathering points, and tourist routes.